2023
DOI: 10.1007/s40820-023-01144-z
|View full text |Cite
|
Sign up to set email alerts
|

"Three-in-One" Multi-Scale Structural Design of Carbon Fiber-Based Composites for Personal Electromagnetic Protection and Thermal Management

Abstract: Wearable devices with efficient thermal management and electromagnetic interference (EMI) shielding are highly desirable for improving human comfort and safety. Herein, a multifunctional wearable carbon fibers (CF) @ polyaniline (PANI) / silver nanowires (Ag NWs) composites with a “branch-trunk” interlocked micro/nanostructure were achieved through "three-in-one" multi-scale design. The reasonable assembly of the three kinds of one-dimensional (1D) materials can fully exert their excellent properties i.e., the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…According to eq , the dielectric loss mechanism mainly encompasses polarization loss ( ε p ) and resistance loss ( ε σ ). The resistance loss is proportional to the conductivity, which in turn is related to the graphitization degree of the MPN-derived PC layer. , From the Raman spectra results, it can be seen that the graphitization degree and resistance loss increase significantly as the pyrolysis temperature increases from 600 to 700 °C/800 °C. The PC in the PC/ZnO-700 and -800 composites can act as a conductive network in the paraffin matrix and promote electron movement, which would result in the generation of microcurrents and consequent electromagnetic wave energy dissipation. , According to the Debye relaxation theory, when the resistance loss is negligible, ε′ and ε″ obey the following equation: true( ε ε s + ε 2 true) 2 + ε 2 = true( ε s ε 2 true) 2 If the ε′−ε″ curve has the form of a semicircle, it can be concluded that the tested material dissipates energy via a polarization relaxation process, and each semicircle corresponds to an individual Debye relaxation process .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…According to eq , the dielectric loss mechanism mainly encompasses polarization loss ( ε p ) and resistance loss ( ε σ ). The resistance loss is proportional to the conductivity, which in turn is related to the graphitization degree of the MPN-derived PC layer. , From the Raman spectra results, it can be seen that the graphitization degree and resistance loss increase significantly as the pyrolysis temperature increases from 600 to 700 °C/800 °C. The PC in the PC/ZnO-700 and -800 composites can act as a conductive network in the paraffin matrix and promote electron movement, which would result in the generation of microcurrents and consequent electromagnetic wave energy dissipation. , According to the Debye relaxation theory, when the resistance loss is negligible, ε′ and ε″ obey the following equation: true( ε ε s + ε 2 true) 2 + ε 2 = true( ε s ε 2 true) 2 If the ε′−ε″ curve has the form of a semicircle, it can be concluded that the tested material dissipates energy via a polarization relaxation process, and each semicircle corresponds to an individual Debye relaxation process .…”
Section: Resultsmentioning
confidence: 98%
“…The resistance loss is proportional to the conductivity, which in turn is related to the graphitization degree of the MPN-derived PC layer. 54,55 From the Raman spectra results, it can be seen that the graphitization degree and resistance loss increase significantly as the pyrolysis temperature increases from 600 to 700 °C/800 °C. The PC in the PC/ZnO-700 and -800 composites can act as a conductive network in the paraffin matrix and promote electron movement, which would result in the generation of microcurrents and consequent electromagnetic wave energy dissipation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the unique porous structure in the NRGO/hollow Ni 0.5 Mg 0.5 Fe 2 O 4 composite aerogel will improve the impedance matching between the absorber and air through regulating the complex permittivity. 24,40,43,44 In addition, when the incident waves penetrate into the 3D porous network structure of the NRGO/hollow Ni 0.5 Mg 0.5 Fe 2 O 4 composite aerogel, multiple reflection will occur at the walls of the holes to attenuate the electromagnetic energy. 19,24,40 Secondly, the structural defects and residual oxygen-containing functional groups on the surfaces of NRGO could act as the polarization centers, resulting in the imbalance of the dipole moment and the formation of dipole polarization under the alternating electromagnetic field, which further improves the microwave attenuation capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, as the PVDF content in the composites increases, ε′ gradually decreases, while ε″ initially increases and subsequently decreases. On the one hand, PVDF is a dielectric material, and its dielectric constant is lower than that of hexagonal flake BaFe 12 O 19 , so an increase in its content will inevitably lead to a decrease in the dielectric constant of the composites. , …”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, PVDF is a dielectric material, and its dielectric constant is lower than that of hexagonal flake BaFe 12 O 19 , so an increase in its content will inevitably lead to a decrease in the dielectric constant of the composites. 32,33 At the same time, PVDF is also an insulating material and does not contribute significantly to conductive losses. Instead, it primarily contributes to polarization losses, including electron polarization, ion polarization, and dipole polarization.…”
Section: Introductionmentioning
confidence: 99%